FXYD5 Is an Essential Mediator of the Inflammatory Response during Lung Injury - Brazee, Patricia L.; Soni, Pritin N.; Tokhtaeva, Elmira; Magnani, Natalia; Yemelyanov, Alex; Perlman, Harris R.; Ridge, Karen M.; Sznajder, Jacob I.; Vagin, Olga; Dada, Laura A. (Frontiers in Immunology, 2017)
The alveolar epithelium secretes cytokines and chemokines that recruit immune cells to the lungs, which is essential for fighting infections but in excess can promote lung injury. Over-expression of FXYD5, a tissue-specific regulator of the Na,K-ATPase, in mice impairs the alveolo-epithelial barrier, and FXYD5 over-expression in renal cells increases C-C chemokine ligand-2 (CCL2) secretion in response to lipopolysaccharide (LPS). The aim of this study was to determine whether FXYD5 contributes to the lung inflammation and injury. Exposure of alveolar epithelial cells (AEC) to LPS increased FXYD5 levels at the plasma membrane, and FXYD5 silencing prevented both the activation of NF-κB and the secretion of cytokines in response to LPS. Intratracheal instillation of LPS into mice increased FXYD5 levels in the lung. FXYD5 over-expression increased the recruitment of interstitial macrophages and classical monocytes to the lung in response to LPS. FXYD5 silencing decreased CCL2 levels, number of cells and protein concentration in broncholaveolar lavage fluid (BALF) after LPS treatment, indicating that FXYD5 is required for the NF-κB-stimulated epithelial production of CCL2, the influx of immune cells, and the increase in alveolo-epithelial permeability in response to LPS. Silencing of FXYD5 also prevented the activation of NF-κB and cytokine secretion in response to interferon α and TNF-α, suggesting that pro-inflammatory effects of FXYD5 are not limited to the LPS-induced pathway. Furthermore, in the absence of other stimuli, FXYD5 over-expression in AEC activated NF-κB and increased cytokine production, while FXYD5 over-expression in mice increased cytokine levels in BALF, indicating that FXYD5 is sufficient to induce the NF-κB-stimulated cytokine secretion by the alveolar epithelium. The FXYD5 over-expression also increased cell counts in BALF, which was prevented by silencing the CCL2 receptor (CCR2), or by treating mice with a CCR2-blocking antibody, confirming that FXYD5-induced CCL2 production leads to the recruitment of monocytes to the lung. Taken together, the data demonstrate that FXYD5 is a key contributor to inflammatory lung injury